I have difficulty to derive the Hessian of the objective function, $l(\theta)$, in logistic regression where $l(\theta)$ is: $$ l(\theta)=\sum_{i=1}^{m} \left[y_{i} \log(h_\theta(x_{i})) + (1- y_{i}) \log (1 - h_\theta(x_{i}))\right] $$

$h_\theta(x)$ is a logistic function. The Hessian is $X^T D X$. I tried to derive it by calculating $\frac{\partial^2 l(\theta)}{\partial \theta_i \partial \theta_j}$, but then it wasn't obvious to me how to get to the matrix notation from $\frac{\partial^2 l(\theta)}{\partial \theta_i \partial \theta_j}$.

Does anybody know any clean and easy way of deriving $X^T D X$?


1 Answer 1


Here I derive all the necessary properties and identities for the solution to be self-contained, but apart from that this derivation is clean and easy. Let us formalize our notation and write the loss function a little more compactly. Consider $m$ samples $\{x_i,y_i\}$ such that $x_i\in\mathbb{R}^d$ and $y_i\in\mathbb{R}$. Recall that in binary logistic regression we typically have the hypothesis function $h_\theta$ be the logistic function. Formally


where $\omega\in\mathbb{R}^d$ and $z_i=\omega^Tx_i$. The loss function (which I believe OP's is missing a negative sign) is then defined as:

$$l(\omega)=\sum_{i=1}^m -\Big( y_i\log\sigma(z_i)+(1-y_i)\log(1-\sigma(z_i))\Big)$$

There are two important properties of the logistic function which I derive here for future reference. First, note that $1-\sigma(z)=1-1/(1+e^{-z})=e^{-z}/(1+e^{-z})=1/(1+e^z)=\sigma(-z)$.

Also note that

\begin{equation} \begin{aligned} \frac{\partial}{\partial z}\sigma(z)=\frac{\partial}{\partial z}(1+e^{-z})^{-1}=e^{-z}(1+e^{-z})^{-2}&=\frac{1}{1+e^{-z}}\frac{e^{-z}}{1+e^{-z}} =\sigma(z)(1-\sigma(z)) \end{aligned} \end{equation}

Instead of taking derivatives with respect to components, here we will work directly with vectors (you can review derivatives with vectors here). The Hessian of the loss function $l(\omega)$ is given by $\vec{\nabla}^2l(\omega)$, but first recall that $\frac{\partial z}{\partial \omega} = \frac{x^T\omega}{\partial \omega}=x^T$ and $\frac{\partial z}{\partial \omega^T}=\frac{\partial \omega^Tx}{\partial \omega ^T} = x$.

Let $l_i(\omega)=-y_i\log\sigma(z_i)-(1-y_i)\log(1-\sigma(z_i))$. Using the properties we derived above and the chain rule

\begin{equation} \begin{aligned} \frac{\partial \log\sigma(z_i)}{\partial \omega^T} &= \frac{1}{\sigma(z_i)}\frac{\partial\sigma(z_i)}{\partial \omega^T} = \frac{1}{\sigma(z_i)}\frac{\partial\sigma(z_i)}{\partial z_i}\frac{\partial z_i}{\partial \omega^T}=(1-\sigma(z_i))x_i\\ \frac{\partial \log(1-\sigma(z_i))}{\partial \omega^T}&= \frac{1}{1-\sigma(z_i)}\frac{\partial(1-\sigma(z_i))}{\partial \omega^T} =-\sigma(z_i)x_i \end{aligned} \end{equation}

It's now trivial to show that

$$\vec{\nabla}l_i(\omega)=\frac{\partial l_i(\omega)}{\partial \omega^T} =-y_ix_i(1-\sigma(z_i))+(1-y_i)x_i\sigma(z_i)=x_i(\sigma(z_i)-y_i)$$


Our last step is to compute the Hessian

$$\vec{\nabla}^2l_i(\omega)=\frac{\partial l_i(\omega)}{\partial \omega\partial \omega^T}=x_ix_i^T\sigma(z_i)(1-\sigma(z_i))$$

For $m$ samples we have $\vec{\nabla}^2l(\omega)=\sum_{i=1}^m x_ix_i^T\sigma(z_i)(1-\sigma(z_i))$. This is equivalent to concatenating column vectors $x_i\in\mathbb{R}^d$ into a matrix $X$ of size $d\times m$ such that $\sum_{i=1}^m x_ix_i^T=XX^T$. The scalar terms are combined in a diagonal matrix $D$ such that $D_{ii}=\sigma(z_i)(1-\sigma(z_i))$. Finally, we conclude that

$$ \vec{H}(\omega)=\vec{\nabla}^2l(\omega)=XDX^T$$

A faster approach can be derived by considering all samples at once from the beginning and instead work with matrix derivatives. As an extra note, with this formulation it's trivial to show that $l(\omega)$ is convex. Let $\delta$ be any vector such that $\delta\in\mathbb{R}^d$. Then

$$\delta^T\vec{H}(\omega)\delta = \delta^T\vec{\nabla}^2l(\omega)\delta = \delta^TXDX^T\delta = \delta^TXD(\delta^TX)^T = \|\delta^TDX\|^2\geq 0$$

since $D>0$ and $\|\delta^TX\|\geq 0$. This implies $H$ is positive-semidefinite and therefore $l$ is convex (but not strongly convex).

  • 5
    $\begingroup$ In the last equation, shouldn't it be $||\delta D^{1/2}X||$ since $XDX^\top$ = $XD^{1/2}(XD^{1/2})^\top$? $\endgroup$
    – appletree
    Commented Sep 4, 2018 at 11:42
  • 2
    $\begingroup$ Shouldn't it be $X^T D X$? $\endgroup$ Commented Feb 3, 2019 at 21:21
  • 3
    $\begingroup$ @ChintanShah No because the answer defined $X$ to be a $d \times m$ matrix that is the concatenation of column vectors $x_i$. This is already the transpose of what is usually the $m \times d$ dimensional design matrix used in stats. $\endgroup$
    – gowrath
    Commented Apr 21, 2020 at 14:15
  • $\begingroup$ Re: the missing sign of the loss function you mention, I think the OP's $l$ is actually the log-likelihood (to be maximized), not a loss (to be minimized), and is therefore not missing a minus sign after all. $\endgroup$
    – chsk
    Commented Oct 8, 2021 at 18:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.